A quantum algorithm for pairwise sequence alignment - Khan, Md.Rabiul Islam; Rafid, Shaikh Farhan; Jahan, Raya (Brac University, 2023)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science, 2023.